Revisiting Pathological Classification Criteria for Adult Idiopathic Inflammatory Myopathies: In-Depth Analysis of Muscle Biopsies and Correlation Between Pathological Diagnosis and Clinical Manifestations. Issue 5 (7th March 2018) - Hou, Ying; Luo, Yue-Bei; Dai, Tingjun; Shao, Kai; Li, Wei; Zhao, Yuying; Lu, Jian-Qiang; Yan, Chuanzhu
Abstract: The European Neuromuscular Centre (ENMC) pathological classification criteria of idiopathic inflammatory myopathies (IIMs) are debatable. The aim of this study was to explore their practicability and reproducibility. We conducted a retrospective analysis of 57 cases of IIMs excluding dermatomyositis (DM) and sporadic inclusion body myositis (sIBM) by in-depth analysis of muscle biopsies and comparisons of the clinical characteristics among polymyositis (PM), non-specific myositis (NSM) and necrotizing autoimmune myopathy (NAM). In 57 non-DM/sIBM-IIM cases, 25 were classified as PM, 15 as NSM, and 17 as NAM. Among them, 51 underwent multilevel sectioning examination of biopsies, with pathological changes at different levels warranting diagnostic rectification in 11 patients (21.57%): 4 PM were reclassified as NSM, and 7 NSM as NAM. Applying atypical CD8+ T cells surrounding non-necrotic muscle fibers resulted in diagnostic rectification from NSM to PM in 2 patients; using 20 T cells (instead of 10) as the threshold for the perivascular infiltration led to diagnostic rectification from NSM to NAM in 9 patients. There were no differences in disease duration or treatment outcomes among the subgroups. The strict pathological criteria to distinguish non-DM/sIBM-IIMs are of limited practicability and reproducibility, and may be of limited clinical significance.